Platinum-based alloy catalyst, preparation method thereof and fuel cell
By combining reduced pressure ball milling and reducing calcining treatment, the problem of high amount of platinum-based alloy catalyst in fuel cells is solved, and a platinum-based alloy catalyst with high oxygen reduction reaction activity and stability is prepared, realizing the The particle size is controllable and environmentally friendly production process reduces costs.
Patent Information
- Application Number
- CN202411701975.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-06
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-14
AI Technical Summary
The existing platinum-based alloy catalysts have problems such as excessive usage, expensive price, insufficient stability, complex preparation process, and environmental pollution in fuel cells. In particular, the ball milling method leads to catalyst agglomeration and missing active sites, which affects performance.
By combining reduced pressure ball milling and reducing calcining treatment, the reduced pressure ball milling and reducing calcining reaction are prepared by doping non-metallic elements and transition metal elements in the support material, and reducing calcining treatment. The performance of platinum-based alloy catalyst avoids agglomeration and reduces raw material costs.
The particle size of the platinum-based alloy catalyst is controlled, and the ORR activity is higher than that of commercial catalysts, and the stability is improved, the process is simple and safe, suitable for mass production, and environmentally friendly, which reduces the actual application cost.
Smart Images

Figure CN119315049A_ABST
Abstract
Description
[0001] This article claims the priority of the Chinese patent application filed with the China Patent Office on August 6, 2024 with application number 202411070242.8. The entire contents of the above application are incorporated herein by reference. Technical Field
[0002] The present invention belongs to the technical field of fuel cell materials, and in particular relates to a platinum-based alloy catalyst and a preparation method thereof, and a fuel cell. Background Art
[0003] Platinum-based catalysts have become the catalyst of choice for proton exchange membrane fuel cells (PEMFCs) due to their highly promising oxygen reduction reaction performance (ORR). However, the above catalysts have problems such as excessive dosage and high prices in practical applications. In order to solve the above problems, in recent years, researchers have mostly alloyed some transition metals (M) with platinum metal (Pt). The resulting PtM alloy can not only reduce the amount of Pt, but also greatly improve the catalytic activity of the cathode oxygen reduction reaction in the fuel cell system. Based on this, the development of platinum alloy electrocatalysts is imminent.
[0004] Compared with commercial Pt / C catalysts, although PtM alloys have a significant improvement effect on the cathode oxygen reduction catalytic activity, the stability of the current PtM alloy catalysts is still insufficient. In addition, since the base metals of the PtM alloy catalyst are easily dissolved during the electrochemical process, they will poison the polymers in the fuel cell, thereby deteriorating the stability of the fuel cell. In order to solve the above problems, the prior art discloses the use of doping non-metallic elements (X), single transition metal elements or rare precious metal elements to form PtX catalysts or PtM multi-element alloy catalysts, so as to further improve the activity and stability of the cathode oxygen reduction reaction in the fuel cell system.
[0005] For example, CN116422342A discloses the use of solvent thermal reduction to prepare platinum-based alloy catalysts. This method is the mainstream synthesis method of platinum-based alloy catalysts. Specifically, different platinum-based alloy catalysts are prepared by high-temperature calcination of solids obtained after mixed heating reaction of different metal salts, carriers and reducing solutions. This preparation method has high universality, but the process is cumbersome, and the organic solvent used is harmful to the environment. Therefore, the preparation method of PtM alloy catalyst needs to be optimized under the premise of ensuring the high performance of the catalyst, and the ball milling method came into being. Among them, CN103055895A discloses a method for preparing a core-shell nanoporous platinum-based alloy catalyst, specifically including weighing pure Al powder, pure Pt powder and pure X element powder according to Al-Pt-X (X is at least one of Ni, Co, Cu, Fe or Ti) alloy component ratio, and the weighed pure Al powder, pure Pt powder, and pure X element powder are mechanically alloyed in a ball mill to obtain Al-Pt-X alloy powder; Al-Pt-X alloy powder is dealloyed in alkaline solution and acidic solution successively, and Al element and part of X element are selectively removed therein, so as to obtain a core-shell nanoporous platinum-based alloy catalyst. This method does not need to use an organic solvent and is more environmentally friendly, but directly putting all raw materials into ball milling easily causes the catalyst to agglomerate, so that its active site is missing, resulting in poor performance of the prepared catalyst. In addition, the ball milling method cannot ensure that all precursor materials are evenly dispersed, and there is also a partial agglomeration phenomenon.
[0006] Therefore, there is an urgent need to develop a platinum-based catalyst with controllable particle size and good ORR performance and a preparation method thereof to solve the above problems. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a platinum-based alloy catalyst and a preparation method thereof and a fuel cell. The present invention adopts a method combining reduced pressure ball milling and reduction calcination treatment to prepare a platinum-based alloy catalyst with controllable particle size, good oxygen reduction reaction (ORR) performance and stability without using an organic solvent.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a platinum-based alloy catalyst, the method comprising the following steps:
[0010] The non-metallic element-doped carrier material, the platinum-based precursor and the transition metal-based precursor are subjected to reduced pressure ball milling to obtain a platinum-based alloy catalyst precursor material;
[0011] The platinum-based alloy catalyst precursor material is subjected to reduction calcination treatment to obtain the platinum-based alloy catalyst.
[0012] In the present invention, the reduced pressure ball milling process refers to ball milling process performed under certain pressure conditions, and more preferably, ball milling process performed under vacuum conditions.
[0013] The following technical problems in the prior art are addressed: (1) the preparation of platinum-based catalysts by solvent thermal reduction method will produce organic waste liquid, which pollutes the environment and is not suitable for mass production; (2) platinum-based catalysts prepared by ordinary ball milling method will mostly undergo agglomeration, and the catalyst activity / stability is insufficient, which is not suitable for the actual application process of fuel cells; (3) the synthesis process of other preparation methods is complicated, the cost of raw materials is high, and it is not conducive to large-scale production. Firstly, compared with the ordinary ball milling method, the present invention adopts the reduced pressure ball milling method to prepare platinum-based alloy catalysts for the first time. Under the condition of ensuring that the particle size of the platinum-based alloy catalyst is controllable, the reduced pressure conditions during ball milling can remove excess gas in the pores of the carrier material, so that the platinum-based precursor and the transition metal-based precursor can be fully mixed and highly dispersed in the pores of the carrier material, thereby improving the effective load and dispersion performance of the metal element, and avoiding the phenomenon of catalyst agglomeration during the ball milling process.
[0014] Secondly, the non-metallic elements doped in the carrier material and the transition metal elements have a synergistic effect, which further regulates the ORR performance of the platinum-based alloy catalyst, making its ORR activity higher than that of commercial Pt / C catalysts and commercial binary alloy catalysts (such as PtCo / C catalysts). At the same time, the synergistic effect between the two reduces the surface energy of platinum atoms and transition metal atoms on the surface of alloy nanoparticles, thereby inhibiting the dissolution of platinum particles during the ORR reaction. In addition, transition metal elements can assist the non-metallic elements in the platinum-based alloy catalyst to strengthen the anchoring effect on the alloy nanoparticles, further inhibit the agglomeration, migration and Ostwald ripening process of alloy nanoparticles in the electrochemical process, and greatly improve the ORR stability of the platinum-based alloy catalyst.
[0015] Finally, the preparation method provided by the present invention mainly includes a reduced pressure ball milling method and a reduction calcination method. The process steps are simple and safe, and it is easy to mass produce compared to other processes. At the same time, compared with the solvent thermal reduction method used in the prior art, the preparation method does not require the use of organic solvents and does not produce organic waste liquid. It is environmentally friendly and has low raw material costs, which greatly reduces the cost issues at the practical application level.
[0016] Preferably, the non-metallic element includes nitrogen and / or sulfur.
[0017] Preferably, the support material comprises a carbon material.
[0018] Preferably, the carbon material comprises carbon black.
[0019] Preferably, the carbon black model includes at least one of EC300-JD, EC600-JD, BP-2000 or XC-72.
[0020] Preferably, the preparation method of the non-metallic element-doped carrier material includes a liquid phase doping method or a gas phase doping method.
[0021] Preferably, the process of the liquid phase doping method includes mixing a precursor containing a non-metallic element, a carrier material and a solvent, removing the solvent and then performing a first sintering treatment to obtain the carrier material doped with the non-metallic element.
[0022] Preferably, the precursor containing non-metallic elements includes a precursor containing nitrogen and / or sulfur.
[0023] Preferably, the precursor containing non-metallic elements includes at least one of aniline, polyaniline, melamine, sodium thioglycolate or sodium thioacetate.
[0024] Preferably, the mass ratio of the precursor containing non-metallic elements to the carrier material is 1:(1-4), for example, it can be 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, etc.
[0025] Preferably, the solvent comprises ethanol and water.
[0026] Preferably, the volume ratio of ethanol to water is (1-5):1, for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, etc.
[0027] Preferably, the temperature of the first sintering treatment is 700-900°C, for example, 700°C, 750°C, 800°C, 850°C, 900°C, etc.; the time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h, etc.
[0028] Preferably, the atmosphere of the first sintering process includes an inert atmosphere, such as argon.
[0029] Preferably, the process of the vapor phase doping method includes placing the carrier material in an atmosphere containing non-metallic elements for a second sintering treatment.
[0030] Preferably, the atmosphere containing non-metallic elements includes an atmosphere containing nitrogen and / or sulfur.
[0031] In the present invention, the atmosphere containing nitrogen element includes ammonia; and the atmosphere containing sulfur element includes hydrogen sulfide.
[0032] Preferably, the temperature of the second sintering treatment is 700-900°C, for example, 700°C, 750°C, 800°C, 850°C, 900°C, etc.; the time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h, etc.
[0033] In the present invention, the non-metallic element is doped on the surface of the carrier material in the form of single atoms.
[0034] Preferably, the platinum-based precursor includes any one of chloroplatinic acid, potassium chloroplatinate, platinum acetylacetonate or platinous chloride, or a combination of at least two thereof.
[0035] Preferably, the transition metal-based precursor includes any one of an iron source, a cobalt source, a nickel source, a copper source or a zinc source, or a combination of at least two thereof.
[0036] Preferably, the iron source includes at least one of ferric nitrate, ferric sulfate, ferric chloride or ferric acetylacetonate.
[0037] Preferably, the cobalt source includes at least one of cobalt nitrate, cobalt sulfate, cobalt chloride or cobalt acetylacetonate.
[0038] Preferably, the nickel source includes at least one of nickel nitrate, nickel sulfate, nickel chloride or nickel acetylacetonate.
[0039] Preferably, the copper source includes at least one of copper nitrate, copper sulfate, copper chloride or copper acetylacetonate.
[0040] Preferably, the zinc source comprises at least one of zinc nitrate, zinc sulfate, zinc chloride or zinc acetylacetonate.
[0041] Preferably, the reduced pressure ball milling process further includes adding a surfactant.
[0042] In the present invention, the surfactant and the carrier material doped with non-metallic elements have a synergistic effect, thereby strengthening the anchoring and confinement effect of the platinum-based alloy nanoparticles and preventing the platinum-based alloy nanoparticles from agglomerating during the subsequent reduction and calcination treatment.
[0043] Preferably, the surfactant includes at least one of polyvinyl pyrrolidone, cetyl trimethyl ammonium bromide, cetyl trimethyl ammonium chloride, polyvinyl alcohol or polyacrylamide.
[0044] Preferably, the pressure of the reduced pressure ball milling treatment is 0.1 kpa to 10 kpa, preferably 0.2 kpa to 0.5 kpa, for example, it can be 0.1 kpa, 0.2 kpa, 0.25 kpa, 0.3 kpa, 0.35 kpa, 0.4 kpa, 0.45 kpa, 0.5 kpa, 0.8 kpa, 1 kpa, 1.5 kpa, 2 kpa, 2.5 kpa, 3 kpa, 3.5 kpa, 4 kpa, 4.5 kpa, 5 kpa, 5.5 kpa, 6 kpa, 6.5 kpa, 7 kpa, 7.5 kpa, 8 kpa, 8.5 kpa, 9 kpa, 9.5 kpa, 10 kpa and the like.
[0045] In the present invention, the pressure of the reduced pressure ball milling treatment is regulated so that the material can be fully and evenly ball milled. If the pressure is too low, the material will not be fully ball milled and the raw materials will be unevenly distributed. Otherwise, the morphology and structure of the carrier material will be destroyed, the proportion of mesopores will be reduced, and the proportion of micropores will be increased, thereby reducing the loading capacity of the mesopores for the platinum-based alloy nanoparticles, causing the platinum-based alloy nanoparticles to agglomerate.
[0046] Preferably, the rotation speed of the reduced pressure ball milling treatment is 150-600 r / min, for example, it can be 150 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, etc.; the time is 0.5-6 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, etc.
[0047] Preferably, the ball-to-material ratio of the reduced pressure ball milling treatment is (5-20):1, for example, it can be 5:1, 8:1, 10:1, 12:1, 15:1, 18:1, 20:1, etc.
[0048] Preferably, the reduction calcination treatment is performed under a reducing atmosphere.
[0049] Preferably, the reducing atmosphere includes any one of H2, H2 / Ar, and H2 / N2.
[0050] Preferably, the concentration of H2 in the reducing atmosphere is 2-10%, preferably 5%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and the like.
[0051] Preferably, the temperature of the reduction calcination treatment is 600-950°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, etc.
[0052] Preferably, the heating rate of the reduction calcination treatment is 1 to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.
[0053] Preferably, a post-treatment step is further included after the reduction calcination treatment is completed.
[0054] Preferably, the post-treatment steps include acid washing, water washing, drying treatment and heat treatment in sequence.
[0055] In the present invention, the pickling acid solution exemplarily includes any one of perchloric acid, sulfuric acid or acetic acid with a concentration of 0.1 mol / L.
[0056] Preferably, the heat treatment is performed under a reducing atmosphere.
[0057] Preferably, the reducing atmosphere includes any one of H2, H2 / Ar, and H2 / N2.
[0058] Preferably, the concentration of H2 in the reducing atmosphere is 2-10%, preferably 5%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and the like.
[0059] Preferably, the temperature of the reduction calcination treatment is 200-550°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, etc.
[0060] Preferably, the heating rate of the reduction calcination treatment is 1 to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.
[0061] In a second aspect, the present invention provides a platinum-based alloy catalyst, wherein the platinum-based alloy catalyst is prepared by the method for preparing a platinum-based alloy catalyst according to the first aspect.
[0062] Preferably, the platinum-based alloy catalyst comprises a support material doped with a non-metallic element and platinum-based alloy nanoparticles dispersed on the surface of the support material doped with the non-metallic element.
[0063] Preferably, the average particle size of the platinum-based alloy nanoparticles is 2 to 8 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, etc.
[0064] In the present invention, the platinum-based alloy nanoparticles have a relatively high specific surface area and electrochemically active area. Too large or too small an average particle size will cause a loss in fuel cell performance.
[0065] In the present invention, the platinum-based alloy nanoparticles are platinum-based intermetallic ordered alloys.
[0066] Preferably, based on the total mass of the platinum-based alloy catalyst as 100%, the platinum-based alloy catalyst includes 10-50wt.% of platinum element by mass, 3-30wt.% of transition metal element by mass, 0.1-5wt.% of non-metallic element by mass and the balance carbon, preferably 25-35wt.% of platinum element by mass, 6-10wt.% of transition metal element by mass, 0.5-1wt.% of non-metallic element by mass and the balance carbon.
[0067] In the present invention, the content of the platinum element is 10-50wt.%, preferably 25-35wt.%, for example, it can be 10wt.%, 15wt.%, 20wt.%, 25wt.%, 26wt.%, 27wt.%, 28wt.%, 29wt.%, 30wt.%, 32wt.%, 35wt.%, 38wt.%, 40wt.%, 45wt.%, 50wt.%, etc. Too low a content will lead to lower activity of the platinum-based alloy catalyst, and too high a content will cause the platinum-based alloy catalyst to easily agglomerate during heat treatment, resulting in a decrease in its performance.
[0068] In the present invention, the content of the transition metal element is 3 to 30 wt.%, preferably 6 to 10 wt.%, for example, it can be 3 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, 30 wt.%, etc. If the content is too high or too low, it will not be able to form an ordered intermetallic alloy with platinum atoms, and other metal phases that are not conducive to the oxygen reduction reaction will be produced, thereby reducing the activity of the prepared catalyst.
[0069] In the present invention, the content of the non-metallic element is 0.1-5wt.%, preferably 0.5-1wt.%, for example, it can be 0.1wt.%, 0.2wt.%, 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, etc. If the content is too high, it is easy to cause the structural collapse of the carbon carrier material and the degree of graphitization to decrease, and the stability of the prepared catalyst is also reduced. If the content is too low, the specific electron adsorption of the non-metallic element on the platinum atom will be reduced, thereby reducing its catalytic activity.
[0070] In a third aspect, the present invention provides a fuel cell, wherein the fuel cell comprises a proton exchange membrane, wherein the proton exchange membrane comprises the platinum-based alloy catalyst according to the second aspect.
[0071] Compared with the prior art, the present invention has the following beneficial effects:
[0072] The present invention provides a method for preparing a platinum-based alloy catalyst. First, compared with a common ball milling method, the present invention adopts a reduced pressure ball milling method for the first time to prepare a platinum-based alloy catalyst. Under the condition of ensuring that the particle size of the platinum-based alloy catalyst is controllable, the reduced pressure condition during ball milling can remove excess gas in the pores of a carrier material, so that a platinum-based precursor and a transition metal-based precursor can be fully mixed and highly dispersed in the pores of the carrier material, thereby improving the effective load and dispersion performance of the metal element and avoiding the phenomenon of catalyst agglomeration during the ball milling process.
[0073] Secondly, the non-metallic elements doped in the carrier material and the transition metal elements have a synergistic effect, which further regulates the ORR performance of the platinum-based alloy catalyst, making its ORR activity higher than that of commercial Pt / C catalysts and commercial binary alloy catalysts (such as PtCo / C catalysts). At the same time, the synergistic effect between the two reduces the surface energy of platinum atoms and transition metal atoms on the surface of alloy nanoparticles, thereby inhibiting the dissolution of platinum particles during the ORR reaction. In addition, transition metal elements can assist the non-metallic elements in the platinum-based alloy catalyst to strengthen the anchoring effect on the alloy nanoparticles, further inhibit the agglomeration, migration and Ostwald ripening process of alloy nanoparticles in the electrochemical process, and greatly improve the ORR stability of the platinum-based alloy catalyst.
[0074] Finally, the preparation method provided by the present invention mainly includes a reduced pressure ball milling method and a reduction calcination method. The process steps are simple and safe, and it is easy to mass produce compared to other processes. At the same time, compared with the solvent thermal reduction method used in the prior art, the preparation method does not require the use of organic solvents and does not produce organic waste liquid. It is environmentally friendly and has low raw material costs, which greatly reduces the cost issues at the practical application level. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 The XRD pattern of the platinum-based alloy catalyst provided in Example 1 of the present invention;
[0076] Figure 2 This is a transmission electron microscope image of the platinum-based alloy catalyst provided in Example 1 of the present invention;
[0077] Figure 3 This is a comparison chart of the activities of the platinum-based alloy catalyst provided in Example 1 of the present invention, and commercial Pt / C and commercial PtCo / C;
[0078] Figure 4 ORR forward scanning polarization curves of the platinum-based alloy catalyst provided in Example 1 of the present invention in an O2-saturated HClO4 solution with a concentration of 0.1 mol / L at the initial and every 10,000 cycles of stability testing;
[0079] Figure 5 The mass specific activity and area specific activity of the platinum-based alloy catalyst provided in Example 1 of the present invention at 0.9 V vs. RHE at the initial stage and after every 10,000 cycles of stability testing;
[0080] Figure 6 Cyclic voltammetry curves of the initial and every 10,000 cycles of stability testing of the platinum-based alloy catalyst provided in Example 1 of the present invention;
[0081] Figure 7 This is a comparison chart of ECSA data of the initial and every 10,000 cycles of stability testing of the platinum-based alloy catalyst provided in Example 1 of the present invention;
[0082] Figure 8 XRD and ORR forward scanning polarization curves of the catalyst provided in Comparative Example 1 of the present invention;
[0083] Fig. 9 XRD and ORR forward scanning polarization curves of the catalyst provided in Comparative Example 2 of the present invention;
[0084] Fig.10 XRD and ORR forward scanning polarization curves of the catalyst provided in Comparative Example 3 of the present invention;
[0085] Fig.11 These are the XRD and ORR forward scanning polarization curves of the catalyst provided in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0086] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0087] Example 1
[0088] The present embodiment provides a Pt3Co / NC binary alloy catalyst, wherein the Pt3Co / NC binary alloy catalyst includes a carbon black material doped with an N element and Pt3Co alloy nanoparticles (with an average particle size of 4.2 nm) dispersed on the surface of the carbon black material doped with an N element. Taking the total mass of the Pt3Co / NC binary alloy catalyst as 100%, the Pt3Co / NC binary alloy catalyst includes 31.4 wt.% of platinum element, 3.1 wt.% of cobalt element, 1.0 wt.% of N element and the remainder carbon.
[0089] This embodiment also provides a method for preparing the above-mentioned Pt3Co / NC binary alloy catalyst, which comprises the following steps:
[0090] (1) 5 g of commercial carbon black EC300-JD was placed in a tube furnace and heat treated at 800°C in an ammonia-argon mixed gas atmosphere (NH3 concentration was 5%) for 2 h to obtain N-doped carbon black.
[0091] (2) 4 g of platinum acetylacetonate, 1.2 g of cobalt acetylacetonate, 4 g of polyvinyl pyrrolidone and 4 g of N-doped carbon black were added to a ball mill, and steel balls were added at a ball-to-material ratio of 10:1. The ambient pressure in the ball mill was reduced to 1.0 kPa and the ball mill was placed in a ball mill. The ball mill was decompressed and milled at 300 r / min for 2 h to obtain a platinum-based alloy catalyst precursor material.
[0092] (3) The platinum-based alloy catalyst precursor material obtained by reduced pressure ball milling was heated to 900°C in a hydrogen-argon mixed gas atmosphere (H2 concentration is 5%) at a heating rate of 10°C / min and heat treated for 2 h to obtain Pt3Co / NC.
[0093] (4) The above-mentioned Pt3Co / NC was placed in a perchloric acid solution with a concentration of 0.1 mol / L, stirred evenly, and then heated to 80°C for 1 hour to remove part of the cobalt on the surface of the alloy nanoparticles by acid washing. After the reaction was completed, it was washed with deionized water until neutral and then dried. Finally, it was heated to 400°C at a heating rate of 10°C / min and heat treated for 1 hour in a hydrogen-argon mixed gas atmosphere (H2 concentration was 5%) to obtain a Pt3Co / NC binary alloy catalyst.
[0094] Example 2
[0095] The difference between this embodiment and embodiment 1 is that a Pt3Ni / NC binary alloy catalyst is provided, and in the preparation method, only the cobalt acetylacetonate in step (2) is replaced with an equal mass of nickel acetylacetonate, and the remaining steps remain unchanged, and the rest are the same as in embodiment 1.
[0096] Example 3
[0097] The difference between this embodiment and embodiment 1 is that a Pt3Ni / NC binary alloy catalyst is provided, and in the preparation method, only the cobalt acetylacetonate in step (2) is replaced by nickel acetylacetonate, and the mass of nickel acetylacetonate is 3.6 g, and the remaining steps remain unchanged, and the rest are the same as in embodiment 1.
[0098] Example 4
[0099] The difference between this embodiment and embodiment 1 is that a Pt3Co / SC binary alloy catalyst is provided, and only step (1) in the preparation method is changed as follows: 5 g of commercial carbon black EC300-JD is placed in a tubular furnace and heat treated for 2 h at 800°C in a mixed atmosphere of hydrogen sulfide and argon (the concentration of hydrogen sulfide is 5%) to obtain S-doped carbon black, and the remaining steps remain unchanged and are the same as in embodiment 1.
[0100] Example 5
[0101] The difference between this embodiment and embodiment 1 is that a Pt3Fe / NC binary alloy catalyst is provided, and in the preparation method, only the cobalt acetylacetonate in step (2) is replaced by an equal mass of iron acetylacetonate, and the polyvinyl pyrrolidone is replaced by an equal mass of hexadecyltrimethylammonium bromide, and the remaining steps remain unchanged, and the rest are the same as in embodiment 1.
[0102] Example 6
[0103] The difference between this embodiment and embodiment 1 is that a Pt3CuZn / NC ternary alloy catalyst is provided, and in the preparation method, only the cobalt acetylacetonate in step (2) is replaced by 0.56g of copper acetylacetonate and 0.55g of zinc acetylacetonate, and the rest is the same as embodiment 1.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 1 is that the reduced pressure condition is not used in step (2) of the preparation method, but ball milling is performed in an air atmosphere instead, and the rest is the same as Example 1.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 1 is that polyvinyl pyrrolidone is not added in step (2) of the preparation method, and the rest is the same as Example 1.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 1 is that the treatment of step (1) is not performed in the preparation method, and in step (2), the N-doped carbon black is replaced by an unmodified carbon black material of equal mass, and the rest is the same as Example 1.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 1 is that the treatment of step (1) is not carried out in the preparation method, and step (2) is adjusted to add 4 g of platinum acetylacetonate, 1.2 g of cobalt acetylacetonate, 4 g of polyvinyl pyrrolidone, 1.6 g of dicyandiamide and 4 g of unmodified carbon black to a ball mill, and the remaining steps remain unchanged, and the rest are the same as in Example 1.
[0112] The platinum-based alloy catalyst material provided in Example 1 was tested, and the testing method was as follows:
[0113] X-ray diffraction (XRD) test: The powder sample is evenly flattened in the groove of the quartz plate and placed in the test instrument. The instrument tube voltage and tube current are adjusted to 40kV and 15mA respectively. The test angle is 10°-90° and the scanning speed is 5°min. -1 .
[0114] Rotating disk electrode (RDE) test: 3 mg of catalyst was dispersed in a mixture of 780 μL isopropanol and 200 μL deionized water, and 20 μL of 5% Nafion solution was added. Ultrasonication was performed for 1 hour. 10 μL of the dispersed ink was dropped onto the disk (0.2475 cm 2 ) electrode, fully dried under a baking lamp, and made into 40ug Pt cm -2 The electrode head with catalyst loading was used for testing. The specific electrochemical characterization test was carried out in a standard three-electrode system, with a carbon rod as the counter electrode and a saturated calomel electrode as the reference electrode. The test was carried out at room temperature, and the ORR polarization curve was measured in an O2-saturated HClO4 electrolyte with a concentration of 0.1 mol / L, and the background CV curve was measured in an N2-saturated HClO4 electrolyte with a concentration of 0.1 mol / L. The specific scanning potential was 0.1-1.1 V RHE , the scan rate was 10 mV s -1 In addition, the ORR polarization curve test procedures of commercial Umico PtCo and JM Pt / C catalysts are similar to the above.
[0115] XRD and TEM characterization were performed on Example 1. Figure 1-2It can be seen that Pt3Co is a standard intermetallic ordered alloy, which corresponds one to one with the standard comparison card. TEM shows that the binary Pt3Co alloy nanoparticles are uniformly dispersed on the N-doped carbon support with an average particle size of 4.2nm. The Pt3Co alloy nanoparticles are highly dispersed and uniform.
[0116] The RDE activity and stability test of Example 1 was performed. Figure 3-4 As shown, it can be seen that the initial ORR half-wave potential is 0.93V. After 30,000 cycles of accelerated decay, the half-wave potential only decays by 3.2mV, as shown in Figure 5-7 As shown, the area specific activity (SA) decayed by 16.0%, and the mass specific activity (MA) increased from 0.62AmgPt -1 Down to 0.54AmgPt -1 , decaying by 12.9%. In addition, the ECSA of the catalyst did not change much after 30,000 cycles of accelerated decay. The excellent ORR stability exhibited by the catalyst is due to the reduced pressure ball milling environment and the synergistic effect of the surfactant and the non-metallic elements in the catalyst, which can make the metal atoms evenly and fully dispersed on the carbon carrier; at the same time, the doping of transition metal elements can produce a synergistic effect with the non-metallic elements in the catalyst, which can reduce the surface energy of platinum atoms on the surface of alloy nanoparticles and inhibit the dissolution of platinum and transition metal atoms during the ORR reaction; in addition, the transition metal can assist the non-metallic elements in the catalyst to strengthen the anchoring effect on the alloy nanoparticles, further inhibiting the agglomeration, migration and Ostwald ripening process of the nanoparticles in the electrochemical process, which is conducive to further improving the ORR stability of the catalyst.
[0117] The present invention further conducts comparative experiments on the reduced pressure ball milling environment, surfactants, and non-metallic element components in the platinum-based alloy catalyst to further verify their effects. Using Example 1 as a standard sample, step (2) is changed to ball milling in an air atmosphere to synthesize the catalyst provided in Comparative Example 1, the particle size of which is 5.2 nm, and the alloy nanoparticles agglomerate to a certain extent, such as Figure 8 As shown, its ORR half-wave potential is 0.92 V, and its particle size and activity are not as suitable for actual fuel cell applications as those in Example 1. This comparative example shows that the pressure conditions during reduced pressure ball milling have an impact on the control effects of catalyst particle size, activity, etc.
[0118] The catalyst provided in Comparative Example 2 was synthesized without adding polyvinyl pyrrolidone in step (2). The particle size was relatively large, i.e., 7.6 nm, and the alloy nanoparticles agglomerated, which was not suitable for practical application in fuel cells. Fig. 9 As shown, the ORR half-wave potential of Comparative Example 2 is only 0.84 V. This comparative example shows that the introduction of surfactants in the catalyst preparation process is beneficial to regulating its particle size and electrochemical activity.
[0119] In addition, the present invention verifies the effect and doping method of non-metallic elements. In Comparative Example 3, unmodified carbon black material is used to prepare a catalyst with a particle size of 6.8 nm. Fig.10 As shown, the ORR half-wave potential is 0.89 V, and the particle size and activity are not suitable for practical applications in fuel cells.
[0120] Finally, the present invention cancels the pretreatment step of the carbon black carrier material in Comparative Example 4, and directly adds the nitrogen source during the subsequent ball milling, and the particle size of the prepared catalyst is 6.4 nm. Fig.11 As shown, the ORR half-wave potential is 0.90 V, which is not suitable for practical applications in fuel cells. This further illustrates that the doping method of non-metallic elements has a regulatory effect on the particle size and activity of the catalyst. At the same time, the non-metallic doping method should prioritize the pre-modification of the carbon carrier.
[0121] The average particle size and composition of the platinum-based alloy catalysts provided in Examples 1-6 and Comparative Examples 1-4 of the present invention are shown in Table 1:
[0122] Table 1
[0123]
[0124]
[0125] As shown in Table 1 above, the present invention can suppress the migration and agglomeration of alloy nanoparticles during heat treatment by regulating the pressure conditions during reduced pressure ball milling and the synergistic effect of the surfactant and the non-metallic (N, S) elements in the carrier material, so that the final platinum-based alloy catalyst has a smaller particle size and good electrochemical activity.
[0126] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a platinum-based alloy catalyst, characterized in that: The method comprises the following steps: The non-metallic element-doped carrier material, the platinum-based precursor and the transition metal-based precursor are subjected to reduced pressure ball milling to obtain a platinum-based alloy catalyst precursor material; The platinum-based alloy catalyst precursor material is subjected to reduction calcination treatment to obtain the platinum-based alloy catalyst.
2. The method according to claim 1, characterized in that The non-metallic elements include nitrogen and / or sulfur; Preferably, the support material comprises a carbon material; Preferably, the carbon material comprises carbon black; Preferably, the carbon black model includes at least one of EC300-JD, EC600-JD, BP-2000 or XC-72.
3. The method according to claim 1 or 2, characterized in that: The preparation method of the non-metallic element-doped carrier material includes a liquid phase doping method or a gas phase doping method; Preferably, the process of the liquid phase doping method comprises mixing a precursor containing a non-metallic element, a carrier material and a solvent, removing the solvent and performing a first sintering treatment to obtain the carrier material doped with the non-metallic element; Preferably, the precursor containing non-metallic elements includes a precursor containing nitrogen and / or sulfur; Preferably, the precursor containing non-metallic elements includes at least one of aniline, polyaniline, melamine, sodium thioglycolate or sodium thioacetate; Preferably, the mass ratio of the precursor containing non-metallic elements to the carrier material is 1:(1-4); Preferably, the solvent comprises ethanol and water; Preferably, the volume ratio of ethanol to water is (1-5):1; Preferably, the temperature of the first sintering treatment is 700-900°C and the time is 1-3h; Preferably, the atmosphere of the first sintering treatment comprises an inert atmosphere; Preferably, the process of the gas phase doping method includes placing the carrier material in an atmosphere containing a non-metallic element for a second sintering treatment; Preferably, the atmosphere containing non-metallic elements includes an atmosphere containing nitrogen and / or sulfur; Preferably, the temperature of the second sintering treatment is 700-900° C., and the time is 1-3 hours.
4. The method according to any one of claims 1 to 3, characterized in that The platinum-based precursor includes any one of chloroplatinic acid, potassium chloroplatinate, platinum acetylacetonate or platinous chloride, or a combination of at least two thereof; Preferably, the transition metal-based precursor comprises any one of an iron source, a cobalt source, a nickel source, a copper source or a zinc source, or a combination of at least two thereof; Preferably, the iron source comprises at least one of ferric nitrate, ferric sulfate, ferric chloride or ferric acetylacetonate; Preferably, the cobalt source comprises at least one of cobalt nitrate, cobalt sulfate, cobalt chloride or cobalt acetylacetonate; Preferably, the nickel source comprises at least one of nickel nitrate, nickel sulfate, nickel chloride or nickel acetylacetonate; Preferably, the copper source comprises at least one of copper nitrate, copper sulfate, copper chloride or copper acetylacetonate; Preferably, the zinc source comprises at least one of zinc nitrate, zinc sulfate, zinc chloride or zinc acetylacetonate; Preferably, the reduced pressure ball milling process further comprises adding a surfactant; Preferably, the surfactant includes at least one of polyvinyl pyrrolidone, cetyl trimethyl ammonium bromide, cetyl trimethyl ammonium chloride, polyvinyl alcohol or polyacrylamide.
5. The method according to any one of claims 1 to 4, characterized in that The pressure of the reduced pressure ball milling treatment is 0.1 kpa to 10 kpa, preferably 0.2 kpa to 0.5 kpa; Preferably, the speed of the reduced pressure ball milling treatment is 150 to 600 r / min, and the time is 0.5 to 6 h; Preferably, the ball-to-material ratio of the reduced pressure ball milling process is (5-20):
1.
6. The method according to any one of claims 1 to 5, characterized in that The reduction calcination treatment is carried out in a reducing atmosphere; Preferably, the reducing atmosphere includes any one of H2, H2 / Ar, and H2 / N2; Preferably, the concentration of H2 in the reducing atmosphere is 2-10%, preferably 5%; Preferably, the temperature of the reduction calcination treatment is 600-950°C; Preferably, the heating rate of the reduction calcination treatment is 1 to 10° C. / min.
7. The method according to any one of claims 1 to 6, characterized in that After the reduction calcination treatment, a post-treatment step is also included; Preferably, the post-treatment steps include pickling, water washing, drying and heat treatment in sequence; Preferably, the heat treatment is carried out under a reducing atmosphere; Preferably, the reducing atmosphere includes any one of H2, H2 / Ar, and H2 / N2; Preferably, the concentration of H2 in the reducing atmosphere is 2-10%, preferably 5%; Preferably, the temperature of the reduction calcination treatment is 200-550°C; Preferably, the heating rate of the reduction calcination treatment is 1 to 10° C. / min.
8. A platinum-based alloy catalyst, characterized in that: The platinum-based alloy catalyst is prepared by the method for preparing a platinum-based alloy catalyst according to any one of claims 1-7.
9. The platinum-based alloy catalyst according to claim 8, characterized in that The platinum-based alloy catalyst comprises a carrier material doped with a non-metallic element and platinum-based alloy nanoparticles dispersed on the surface of the carrier material doped with the non-metallic element; Preferably, the average particle size of the platinum-based alloy nanoparticles is 2 to 8 nm; Preferably, based on the total mass of the platinum-based alloy catalyst as 100%, the platinum-based alloy catalyst includes 10-50wt.% of platinum element by mass, 3-30wt.% of transition metal element by mass, 0.1-5wt.% of non-metallic element by mass and the balance carbon, preferably 25-35wt.% of platinum element by mass, 6-10wt.% of transition metal element by mass, 0.5-1wt.% of non-metallic element by mass and the balance carbon.
10. A fuel cell, characterized in that: The fuel cell comprises a proton exchange membrane, and the proton exchange membrane comprises the platinum-based alloy catalyst according to claim 8 or 9.
Citation Information
Patent Citations
Method for preparing core-shell type nano-porous platinum alloy catalyst
CN103055895A
Multi-atom doped surface platinum-rich catalyst and preparation method thereof
CN116422342A
Cited By
Oxygen reduction electrocatalyst as well as preparation method and application thereof
CN119920911A
Gallium-doped platinum-based ordered alloy catalyst as well as preparation method and application thereof
CN120485834A
Ternary platinum-based ordered alloy catalyst, preparation method thereof and fuel cell
CN120690876A